Klasifikasi Genre dan Rating Konten di Netflix : Wawasan dari Analisis Chi-Square dan Clustering - alzahra, alika aziza; Hananto, April Lia; Hananto, Agustia; Priyatna, Bayu (Universitas Multi Data Palembang, 2025)
Streaming platforms like Netflix rely on genre classification and content rating to enhance user experience and develop more effective marketing strategies. This study aims to analyze the relationship between genre and content rating on Netflix using Chi-Square analysis and clustering techniques to group genres based on rating distribution patterns. The Chi-Square test results indicate a significant relationship between genre and content rating (p-value < 0.05), suggesting that certain types of content tend to receive specific ratings. Furthermore, clustering analysis identifies three main groups: genres with high ratings suitable for a broad audience, genres with varied ratings that are more subjective, and genres with lower ratings that often include adult or less popular content. These findings provide insights that Netflix can leverage to optimize its content catalog, develop personalized recommendations, and tailor marketing strategies based on user consumption patterns.